Longitudinal Measurements of Inflammatory Indices During Treatment for Locally Advanced Rectal Cancer and Associations with Smoking, Ethnicity and Pathological Response - Nancy Huang; Joseph Descallar; Wei Chua; Weng Ng; Emilia Ip; Christopher Henderson; Tara L. Roberts; Stephanie Hui-Su Lim (Radiation)
This study explores the change in inflammatory markers over the course of neoadjuvant chemoradiation and adjuvant chemotherapy for LARC and assesses the association with clinicopathological factors at pre-specified time-points. We examined the trends of neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), C-reactive protein (CRP), carcinoembryonic antigen (CEA), fibrinogen, and albumin through multilevel modelling of 29 prospective LARC patients across six time-points: before neoadjuvant chemoradiation (T1), week 3 of chemoradiation (T2), post-chemoradiation (T3), post-surgery (T4), midpoint of adjuvant chemotherapy (T5), and chemotherapy completion (T6). Variables collected included ethnic background, body mass index (BMI), smoking status, and pathological responses graded by Ryan tumour regression grade and pathological tumour and nodal status. NLR and PLR demonstrated an increasing trend during chemoradiation. Median CEA was highest at baseline and lowest at T4. The highest median values for NLR, PLR, CRP, and fibrinogen were at T4. Smokers demonstrated a trend towards a higher NLR compared to non-smokers. NLR was significantly higher in Caucasians compared to Asians at T2. Patients with pathological node-negative status had a higher NLR at T5 and T6 and a higher PLR at T1, T3, T5 and T6. Overall, inflammatory indices change dynamically throughout treatment and vary with clinicopathological factors.